Solidarity divided. The crisis in organized labor and a new path toward social justice - Fletcher, Bill; Gapasin, Fernando (Berkeley, 2008)
"The U.S. trade union movement finds itself today on a global battlefield filled with landmines and littered with the bodies of various social movements and struggles. Candid, incisive, and accessible, Solidarity Divided is a critical examination of labor's current crisis and a plan for a bold new way forward into the twenty-first century. Bill Fletcher and Fernando Gapasin, two longtime union insiders whose experiences as activists of color grant them a unique vantage on the problems now facing U.S. labor, offer a remarkable mix of vivid history and probing analysis. They chart changes in U.S. manufacturing, examine the onslaught of globalization, consider the influence of the environment on labor, and provide the first broad analysis of the fallout from the 2000 and 2004 elections on the U.S. labor movement. Ultimately calling for a wide-ranging reexamination of the ideological and structural underpinnings of today's labor movement, this is essential reading for understanding how the battle for social justice can be fought and won. "